The Relationship Between Maternal Childbirth Experience and the Success of Early Initiation of Breastfeeding: Biological Perspectives and Implications for Student Learning in Postpartum Mothers - Elfira Sri Futriani; Dini Oktaviani Soleha; Komala Sari; Suherni Suherni; Maulida Fitria; Sakinah Mawadah Warahmah (Jurnal Penelitian Pendidikan IPA, 2025)
The success of early initiation of breastfeeding (EIBF) is influenced by maternal childbirth experience, which significantly impacts postpartum mothers' ability to implement appropriate breastfeeding practices. Primiparous mothers are often at a greater disadvantage due to their limited prior experience and lack of understanding about the importance of early breastfeeding initiation. This study aims to examine the relationship between maternal childbirth experience and the success of EIBF, with a focus on the physiological aspects of lactation and its implications for health science education. Quantitative design with an analytical cross-sectional approach was employed. Primary data were collected using questionnaires, and statistical analyses were conducted with univariate and bivariate tests using the Chi-Square method in SPSS version 26.0. The results showed that the majority of respondents were multiparous (56.7%, n=17), while 43.3% (n=13) were primiparous. The Chi-Square test yielded a p-value of 0.027 (<0.05), indicating a significant association between maternal childbirth experience and the success of EIBF. These findings suggest that primiparous mothers face more challenges in initiating breastfeeding early due to a lack of prior experience. However, participation in antenatal care (ANC) and pregnancy classes can improve knowledge and skills, thus enhancing the likelihood of successful EIBF implementation. This research contributes to the field of health science education by highlighting the importance of understanding lactation physiology and increasing postpartum mothers' scientific literacy, which can be applied in both health practice and education.